Brønsted imidazolium ionic liquids: Synthesis and comparison of their catalytic activities as pre-catalyst for biodiesel production through two stage process - C.D., Wilfred (Elsevier, 2011)
In the present work, study was undertaken to prepare biodiesel via a two-step transesterification process. The high free fatty acids (FFA) value contained in the crude palm oil (CPO), which cause several problems with the straight alkaline-catalyzed, were converted to fatty acid methyl esters (FAME) before introducing KOH-catalyzed transesterification step. In order to evaluate their catalytic activities, three Brønsted acidic imidazoliums were investigated. These ionic liquids (ILs) appeared to be promising candidates to replace conventional acidic catalyst for biodiesel production due to their unique properties. Among them, a longer side chains 1-butyl-3-methyl-imidazolium hydrogensulfate (BMIMHSO4) was found to be more superior to the other two catalysts. Based on the experimental results, a catalyst (BIMHSO4) concentration of 4.5 wt.%, methanol/CPO molar ratio of 12:1, a temperature of 160 C, and agitation speed of 600 rpm provided a final CPO acid value lower than 1.0 mg KOH/CPO within 120 min. The second alkalicatalyze step was performed at agitation speed of 600 rpm, 60 C, 1.0% KOH for 50 min. The final biodiesel product in 98.4% yield was analyzed by gas chromatography (GC). The determined physicochemical important properties of POME were confirmed with American Standards for Testing Material (ASTM).